Sosialisasi dan Edukasi Pemanfaatan Platelet Rich Plasma (PRP) Metode Nebulisasi pada Paguyuban Lansia PMI Kota Semarang - Syafira, Mutia; Anzhari, Della Hashfi; Ariani, Resti; Hastuti, Diah; Shafira, Chintya Meiska; Amirullah, Nafissa Naomi (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Based on the results of initial observations conducted with activity partners, it was found that the Semarang City PMI Elderly Association still has limited knowledge regarding innovations in the use of blood-based products, especially Platelet Rich Plasma (PRP), and its application methods in the health sector. The lack of information that is easily understood by the elderly group is one of the factors in low health literacy regarding the development of blood-based health technology. This community service activity aims to socialize and educate the Semarang City PMI Elderly Association regarding the concept, benefits, and basic principles of the use of Platelet Rich Plasma (PRP) with the nebulization method. The activity was implemented through educational and interactive material delivery, discussions, and evaluation of participant understanding. Based on the results of the community service activity, participants showed high enthusiasm and consistent attendance during the socialization process, marked by active participation in discussions and increased understanding of the material presented. This activity can be concluded as running well and showing a better understanding based on qualitative analysis and elderly awareness of the innovation of PRP use as part of health education. This community service activity is expected to support the role of universities in the implementation of Tridarma, especially community service in the health sector.